PERANCANGAN SISTEM INFORMASI PENJUALAN BARANG BERBASIS VISUAL STUDI KASUS DI TB. BERKAH KERAMIK - Rizki Dea Anthalia Yustina (Universitas Sains dan Teknologi Komputer, 2024)
TB. Berkah Keramik is a company that operates in the sales of building materials. The address is H2 Sido Mukti, precisely on Jl. Lintas Rawa Jitu, Aji Baru Building, Tulang Bawang, Lampung. This company was founded in 2019. TB. Until now TB. Berkah Keramik in managing sales, sales transactions and managing goods still uses manual methods written on note paper and bookkeeping. In recording, problems often occur, such as in the example of a sales note, an error occurs when recording the nominal price, making it susceptible to errors in calculations.In this research the author uses a cash-based accounting method (Accrual Basis). Accrual Basis is the process of recording accounting transactions where transactions are recorded when cash is received or when cash is paid out. The use of the Accrual Basis Method in this research is due to TB Transactions. Ceramic Blessings are done in cash. in this research for system development. The research method used by the author in this research is Research and Development (R&D). Research and Development (R&D) is a research method used to produce certain products and test the product's effectiveness.The results of this research are in the form of Visual-based Sales Information System Software. This system can help cashiers in managing and reporting sales. As well as making it easier for owners to check sales reports and financial reports. By designing a new system, sales management will be more effective. With this, the author developed a goods sales system using the VB.Net programming language (Visual Basic 2010) and MySQL information as the database. And crystal reports to create transaction reports, so that they can help and make things easier for users. This can be proven by testing the effectiveness of the performance of the old system compared to the new system, if the percentage is 40.00% : 90.00%.